2021
DOI: 10.1177/09749101211049038
|View full text |Cite
|
Sign up to set email alerts
|

Shadow Economy and Environmental Pollution in West African Countries: The Role of Institutions

Abstract: This study deviates from extant studies by examining the effect of shadow economy (SE) on environmental pollution, and the role institutional indicators play in moderating the effect in West Africa between 1992 and 2015. Specifically, the study employed three institutional indicators (corruption control [COR], law and order [LAW], and bureaucratic quality [BUQ]) to mediate the effect and also determine its threshold values. SE is measured using Multiple Indicators Multiple Causes (MIMIC) while environmental po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 102 publications
1
14
0
Order By: Relevance
“…Similarly, an increase in economic growth also comes with both production and consumption wastes which deteriorate long-run environmental quality. The short-run result of negative effect of economic growth on ecological footprint is supported by the finding of Danish et al (2019), while the long-run result is in tandem with the works of Uddin et al (2017), Mrabe et al (2017), Zafar et al (2019), Ibrahiem and Hanafy (2020), Usman et al (2021a, b), Yang et al (2021a) and Dada et al (2021b) whose findings conclude that economic growth degenerates the environment.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Similarly, an increase in economic growth also comes with both production and consumption wastes which deteriorate long-run environmental quality. The short-run result of negative effect of economic growth on ecological footprint is supported by the finding of Danish et al (2019), while the long-run result is in tandem with the works of Uddin et al (2017), Mrabe et al (2017), Zafar et al (2019), Ibrahiem and Hanafy (2020), Usman et al (2021a, b), Yang et al (2021a) and Dada et al (2021b) whose findings conclude that economic growth degenerates the environment.…”
Section: Resultsmentioning
confidence: 80%
“…The positive effect of trade openness on EFP aligns with the submissions of Al-Mulali et al (2015), Le et al (2016) and Dada and Akinlo (2021) who conclude that trade openness spurs environmental degradation. Nevertheless, studies by Chen et al (2018), Fakher (2019) and Dada et al (2021a, b) found that trade openness improves environmental quality. Population (proxy by population growth rate) has different significant effects on EFP in the short run, while in the long run, the effects are not significant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…West Africa provides an interesting study area, being one of the regions with the highest level of shadow economy (Dada et.al. 2021b), and also ICT penetration has begun to gain momentum in the region (ITU 2018; Akinlo and Dada 2021). In addition, the prevalence of ICT in the region, especially internet penetration in terms of mobile and broadband connectivity, has become an important policy objective of the government in addressing the issue of crime and shadow economy.…”
Section: Introductionmentioning
confidence: 99%